2019
DOI: 10.1186/s41182-019-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Malaria hot spot along the foothills of Rakhine state, Myanmar: geospatial distribution of malaria cases in townships targeted for malaria elimination

Abstract: BackgroundMyanmar has targeted elimination of malaria by 2030. In three targeted townships of Rakhine state of Myanmar, a project is being piloted to eliminate malaria by 2025. The comprehensive case investigation (CCI) and geotagging of cases by health workers is a core activity under the project. However, the CCI data is not analyzed for obtaining information on geospatial distribution of cases and timeliness of diagnosis. In this regard, we aimed to depict geospatial distribution and assess the proportion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Our analyses also showed malaria to peak and cluster temporally from approximately May and into November. This corresponds with the rainy season in Myanmar, and the pattern has been well-described in several other studies [ 14 , 44 ]. A second peak was apparent in some high burden states/regions (especially Rakhine and Chin states).…”
Section: Discussionsupporting
confidence: 82%
“…Our analyses also showed malaria to peak and cluster temporally from approximately May and into November. This corresponds with the rainy season in Myanmar, and the pattern has been well-described in several other studies [ 14 , 44 ]. A second peak was apparent in some high burden states/regions (especially Rakhine and Chin states).…”
Section: Discussionsupporting
confidence: 82%
“…Our analyses also showed malaria to peak and cluster temporally from approximately May and into November. This corresponds with the rainy season in Myanmar, and the pattern has been well-described in several other studies [40,41]. A second peak was apparent in some high burden states/regions (especially Rakhine and Chin states).…”
Section: Discussionsupporting
confidence: 82%
“… 50 , 84 86 A study in the forested area of northern Myanmar bordering with China suggested that the scenario was different from other parts of Southeast Asia such that the high altitude leads to low temperature and thus less malaria vector, whereas malaria vector normally occurs in lowlands, foothills, and mid-hills some distance away of forest. 87 , 88 According to the experts in this study, forest was not suitable for mosquito proliferation. Unfortunately, with some limitation of data availability in this study, the developed model in this study was based on the forest factor coded as a binomial variable (0 or 1) rather than the distance to forest.…”
Section: Discussionmentioning
confidence: 92%